2016
DOI: 10.1161/strokeaha.116.013340
|View full text |Cite
|
Sign up to set email alerts
|

PPM1A Methylation Is Associated With Vascular Recurrence in Aspirin-Treated Patients

Abstract: Background and Purpose— Despite great efforts by pharmacogenetic studies, the causes of aspirin failure to prevent the recurrence of ischemic events remain unclear. Our aim was to study whether epigenetics could be associated with the risk of vascular recurrence in aspirin-treated stroke patients. Methods— We performed an epigenetic joint analysis study in 327 patients treated with aspirin. In the discovery stage, we performed a nested case–control stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 17 publications
1
23
0
Order By: Relevance
“…Hypermethylation of ApoE cerebrovascular diseases [61]. The hypomethylation of TNF receptor-associated factor 3 (TRAF3) and of protein phosphatase 1A (PPM1A) is also related to increased stroke occurrence in patients treated with antiplatelet drugs [62,63]. and VCAM-1 expression may be considered as an early event in the etiology of cardiovascular and cerebrovascular diseases [61].…”
Section: Study Model Condition/effects Outcomes Referencesmentioning
confidence: 99%
See 3 more Smart Citations
“…Hypermethylation of ApoE cerebrovascular diseases [61]. The hypomethylation of TNF receptor-associated factor 3 (TRAF3) and of protein phosphatase 1A (PPM1A) is also related to increased stroke occurrence in patients treated with antiplatelet drugs [62,63]. and VCAM-1 expression may be considered as an early event in the etiology of cardiovascular and cerebrovascular diseases [61].…”
Section: Study Model Condition/effects Outcomes Referencesmentioning
confidence: 99%
“…and VCAM-1 expression may be considered as an early event in the etiology of cardiovascular and cerebrovascular diseases [61]. The hypomethylation of TNF receptor-associated factor 3 (TRAF3) and of protein phosphatase 1A (PPM1A) is also related to increased stroke occurrence in patients treated with antiplatelet drugs [62,63]. Atherosclerotic cerebral infarction [56,57] Stroke patients Hypermethylation of CDKN2B prevalent ischemic heart disease or stroke.…”
Section: Study Model Condition/effects Outcomes Referencesmentioning
confidence: 99%
See 2 more Smart Citations
“…DNA methylation in specific genes can also be helpful to predict response to a specific treatment. Two elegant studies by Gallego-Fabrega et al have shown that changes in DNA methylation patterns of PPM1A and TRAF3 are, respectively, associated with vascular recurrence in aspirin-treated patients and clopidogrel response and recurrence of ischemic events in patients with stroke [25, 26]. …”
Section: Dna Methylationmentioning
confidence: 99%